Regulation of the MEI-1/MEI-2 Microtubule-Severing Katanin Complex in Early Caenorhabditis elegans Development. Issue 10 (1st October 2016) - Beard, Sarah M; Smit, Ryan B; Chan, Benjamin G; Mains, Paul E
Abstract: After fertilization, rapid changes of the Caenorhabditis elegans cytoskeleton occur in the transition from meiosis to mitosis, requiring precise regulation. The MEI-1 /MEI-2 katanin microtubule-severing complex is essential for meiotic spindle formation but must be quickly inactivated to allow for proper formation of the mitotic spindle. MEI-1 /MEI-2 inactivation is dependent on multiple redundant pathways. The primary pathway employs the MEL-26 substrate adaptor for the CUL-3 /cullin-based E3 ubiquitin ligase, which targets MEI-1 for proteosomal degradation. Here, we used quantitative antibody staining to measure MEI-1 levels to determine how other genes implicated in MEI-1 regulation act relative to CUL-3 /MEL-26 . The anaphase-promoting complex/cyclosome, APC/C, the DYRK (Dual-specificity tyrosine-regulated kinase), MBK-2, and the CUL-2 -based E3 ubiquitin ligase act together to degrade MEI-1, in parallel to MEL-26 /CUL-3 . CUL-2 is known to keep MEL-26 low during meiosis, so CUL-2 apparently changes its target from MEL-26 in meiosis to MEI-1 in mitosis. RFL-1, an activator of cullin E3 ubiquitin ligases, activates CUL-2 but not CUL-3 for MEI-1 elimination. HECD-1 (HECT/Homologous to the E6AP carboxyl terminus domain) E3 ligase acts as a MEI-1 activator in meiosis but functions as an inhibitor during mitosis, without affecting levels of MEI-1 or MEI-2 . Our results highlight the multiple layers of MEI-1 regulation that are required during the switch from the meiotic to mitotic modes of cell division.